Consumptive hypothyroidism complicating infantile hepatic hemangioma successfully treated with propranolol: a case report and literature review - Irene Bettini; Giulia Poletti; Alessandro Rocca; Valeria Di Natale; Monia Gennari; Marcello Lanari; Andrea Pession; Alessandra Cassio (Italian Journal of Pediatrics)
Abstract Background Consumptive hypothyroidism (CH) is a rare paraneoplastic syndrome, caused by the overexpression in vascular tumors of type 3 deiodinase (D3), converting thyroid hormones into inactive metabolites. Case presentation We report the case of a 2-months-old male infant with diffuse infantile hepatic hemangioma (IHH). Thyroid function screening detected a CH. The patient was promptly treated with propranolol: after 2 weeks, a marked reduction in tumour size was observed and thyroid function was restored. No hormone replacement therapy was required. We then performed a literature review on PubMed/Medline: based on the title and abstract, we extracted 64 cases of CH secondary to IHH published between 2000 and 2023. 59.37% patients received propranolol, either alone (52.63%) or in combination with other treatments. 18.75% patients required surgical treatment or liver transplant. LT4 was administered in 92.85% of the patients. Patients who received propranolol required a lower dosage of LT4 than patients who received other treatments. Conclusions Thyroid function should be evaluated in all children with IHH to rule out CH. Early recognition of IHH and CH and prompt therapy with propranolol can effectively treat IHH and the subsequent hypothyroidism, sometimes even without the need of hormone replacement therapy.